PENGARUH PENGALAMAN KERJA, GAYA KEPEMIMPINAN, KOMPETENSI, DAN INTEGRITAS TERHADAP KUALITAS KEPUTUSAN KARYAWAN DI JURUSAN ADMINISTRASI NIAGA POLINEMA - Tri Yulistyawati Evelina; Shinta Maharani Trivena; Ahmad Fauzi (Adbis: Jurnal Administrasi dan Bisnis, 2019)
The research aims to examine the Effect of Work Experience, Leadership Style, Competence, and Integrity on the Quality of Employee Decisions in the Department of Commerce of the State Polytechnic of Malang. The type of data used is primary data (questionnaire) and secondary data. This research involved employees in the Department of Commerce Administration. The results of the three leadership styles studied, namely the Autocratic, Participative and Laissez-faire leadership styles, then who have the most significant influence are the Autocratic and Participatory Leadership Styles.